The handbook of crisis communication - Coombs, W. Timothy; Holladay, Sherry J. (Hoboken, New Jersey John Wiley & Sons, Ltd., 2023)
"Written as a tool for both researchers and communication managers, The Handbook of Crisis Communication is a comprehensive examination of the latest research, methods, and critical issues in crisis communication. Incorporating the views and research of more than 50 top scholars, the book provides a starting point for developing crisis communication as a distinctive field research rather than as a sub-discipline of public relations or corporate communication. Going beyond traditional applications, the Handbook also explores the key emerging areas of new technology and global crisis communication. Designed to improve the practice of crisis communication, The Handbook of Crisis Communication provides a collection of approaches and insights into crisis communication that informs the work of practitioners, with applied research to make crisis communication more effective. It also offers a resource for crisis communication researchers, including various methods of studying crisis communication and suggestions for future research. Updates in this second edition include new and revised case studies, discussion of the latest terminology and methods, new scenarios for students and practitioners to consider, and more"
Revised edition of The handbook of crisis communication, 2010.
Includes bibliographical references and index.
Keywords: Communication in management; Crisis management